Keratinocyte sheets prepared with temperature-responsive dishes show enhanced survival after in vivo grafting on acellular dermal matrices in a rat model of staged bi-layered skin reconstruction - Matsumine, Hajime (Regen Ther, 2019)
INTRODUCTION: Bi-layered skin reconstruction can be achieved by staged grafting of acellular dermal matrices (ADMs) and cultured epithelial keratinocyte sheets (KSs). Both KSs and ADMs have been used for long; yet, their combined use has shown poor effectiveness. This outcome has been related to the enzymatic treatment used in the preparation of KSs, which impairs their adhesion potential to ADMs and the formation of a basement membrane (BM). Temperature-responsive (TR) culture dishes allow for enzyme-free preparation of KSs with preservation of BMs and intercellular adhesion proteins; yet, their use has not been previously applied to staged bi-layered skin reconstruction. Using an in vivo rat model, we tested the hypothesis that TR cultures enhance KSs survival and BM preservation after sequential grafting on ADMs. METHODS: In nude rats (n = 9/group), a 9-cm [2] full-thickness dorsal skin defect was repaired with a commercial ADM. At 2 weeks after surgery, we grafted the ADM with KSs (circular, 25 mm diameter), prepared from human cells either by enzymatic Dispase treatment (DT control group) or a TR culture dish (TR experimental group). KSs survival and BMs preservation was assessed one week later by digital imaging, histology (hematoxylin & eosin), immunohistochemistry (collagen IV, pancytokeratins) and immunofluorescence (cytokeratin 1-5-6, laminin). RESULTS: The TR group showed a significantly higher KSs survival (120 ± 49 vs. 63 ± 42 mm(2); p < 0.05) and epidermal thickness (165 ± 79 vs. 65 ± 54 μm; p < 0.01) compared with the control DT group, as well as higher epidermal maturation (cytokeratin) and a denser laminin and Collagen IV expression in the BMs in vitro and in vivo. CONCLUSION: These findings suggest that KSs prepared with TR culture dishes have significantly enhanced survival when grafted on ADMs; these outcomes could help improve current clinical strategies in wound care by skin reconstruction.